Accountability of pondok pesantren; a systematic literature review - Ahmad Nurkhin; Abdul Rohman; Tri Jatmiko Wahyu Prabowo (Cogent Business & Management, 2024)
This article presents the systematic literature review (SLR) of accountability of pondok pesantren (Islamic boarding school). The purpose is to provide a review of the existing literature (theoretical/empirical) on the accountability of pondok pesantren and to analyze the future agenda of research. By using the Publish or Perish application, 200 units of initial article data were obtained for further analysis. The results showed that there were few reputable international journal articles (indexed by Scopus) that published articles on the topic of pondok pesantren accountability and focused more on financial management. The other related topics are accounting and financial reports, governance and accountability in Islamic organizations. The qualitative research method was more used and shows that accountability of pondok pesantren applied double accountability (responsibility to God and to others). Furthermore, it was found that the relevance of accountability for pondok pesantren with local cultural values other than Islamic values as a basis. In addition, the theory that was often used as a basis for accountability of pondok pesantren was legitimacy theory. The topics for the future research agenda on accountability of pondok pesantren is accountability of asset management and analysis the determinant of pondok pesantren accountability.
Keywords: 650; Accountability; financial management; pondok pesantren; governance; SLR